(3MOhK GdMQhas - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI bGd (B: (3GdMeO ddg MeOkG SJMb dYXeI PGJg hHYO adjS cd bGFd HYOJg eJMJGHkG EdjgG hdG cd WGdH Yfg aGbOkG dgG GdaUd GdChd ai SHH MOhK s
(3BNQgG (B:s
(3hGdHGA Yf bdY GdCLSGe GddHfg GdeJdGUbI HYVgG Yf HYV s
(3Vef eLehY , JQJjHgG (B: 1s
(3edc eMeO Hf ehSj GdMGaXs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdadSaI hGdefWbs